AKUNTABILITAS PENGELOLAAN DANA DESA DALAM UPAYA MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA DI KECAMATAN JANGKA - Khalil Gibran; Syahril Jaddang; Muh Ardiansyah (CV ODIS, 2021)
The welfare of society is a very complex issue. The reality of the low level of welfare of society was felt by our ancestors, even though as we know that the potential for natural resources of Indonesia is very abundant. The high poverty rate is still haunting the national development issue. Following up on this problem, the government has made efforts to formulating and implementing a national development strategy to overcome the reality of the low level of welfare of society by implementing development on village development-oriented, namely through the allocation of village funds for each year. To achieve this goal, the government hopes that village funds can be managed accountably. This study aims to investigate the accountability of village fund management and to evaluate the efforts made by the village government to improve the welfare of society in the term district. This research is qualitative research with a phenomenological approach. The results showed that the management of village funds ranging from planning, implementation, administration, reporting to accountability activities had not fully fulfilled the principle of accountability and the welfare indicators tested showed that the villagers were not yet fully prosperous. There are still villages that have not prioritized the management of village funds for villager empowerment programs so that the efforts of the village government to improve welfare are not optimal.